Swarm, evolutionary, and memetic computing : 6th International Conference, SEMCCO 2015, Hyderabad, India, December 18-19, 2015, revised selected papers /: 6th International Conference, SEMCCO 2015, Hyderabad, India, December 18-19, 2015, revised selected papers. ([2016]) - Unknown
No abstract available